Professional Quality Work Life among Nurses in Intensive Care Units - Murtadha Khudair Turfi; Mohammed Al-Jubouri (Kufa Journal for Nursing Sciences)
Background: professional quality work-life, as one of the most important issues in the nursing profession, can negatively affect the healthcare system. Purpose: To examine the professional quality work life. Method: A descriptive cross-sectional study a non-probability sampling method used and total sample collected was (126) of ICU nurses. Results: Burnout, Secondary Traumatic Stress, and, Compassion Satisfaction among intensive care units nurses were moderate. Conclusion & Recommendation: Nurses in ICUs suffered from moderate Burnout and Secondary Traumatic Stress, and the result can be negative effects on the quality of care. Although nurses' Compassion Satisfaction, it is still an important issue that nurses may face in intensive care units.